State of the Heart: CMR in Coronary Artery Disease - Faridah Abdul Aziz, Yang; Fadzli, Farhana; Rizal Azman, Raja; Mohamed Sani, Fadhli; Vijayananthan, Anushya; Nazri, Mohammad (Current Medical Imaging, 2013)
The application of magnetic resonance imaging (MRI) in evaluating the heart and its plethora of diseases has grown over the years. Abundant research and advancements in this modality had been made, largely due to the perceived benefits of MRI. These accepted advantages of MRI include absence of ionizing radiation, reproducible technique and does not require iodine-based contrast media. It had even been touted as the ‘one-stop shop’ for cardiac imaging. Cardiac magnetic resonance (CMR) has the ability to assess the heart comprehensively, examining cardiac morphology, ventricular function, perfusion, myocardial viability, as well as delineation and quantification of tissue constituents. Other benefits lie in the intrinsic properties of MRI which provide high temporal and spatial resolution, superb tissue contrast and possibility of imaging in any plane. In view of these superior advantages of CMR, it is currently the modality of choice in a number of cardiac diseases.
Keywords: magnetic resonance